Dampak Trauma Masa Kecil dalam Memulihkan Kesehatan Mental Mahasiswa - Mardiyah, Ainul; Haikal, Fakhrel; Ramadhani, Sarah; Tarigan, Juliani Br (Madani: Jurnal Ilmiah Multidisiplin, 2026)
Childhood trauma is a negative early-life experience that can significantly disrupt an individual’s psychological development and influence later stages of life. This study aims to analyze the impact of childhood trauma on the mental health recovery process of university students. The focus of this research includes the types of trauma experienced, the psychological mechanisms affected, and the challenges that arise during the recovery process within the academic environment. This study employs a qualitative approach using in-depth interviews with students who have a history of childhood traumatic experiences. The findings indicate that childhood trauma can impair emotional regulation, increase levels of anxiety and academic stress, and reduce self-confidence in forming social relationships on campus. Nevertheless, social support, counseling services, and a responsive campus environment play a crucial role in strengthening students’ mental health recovery. These results highlight the importance of early trauma intervention and adequate psychological support services to promote long-term mental well-being among university students.